End of days [large type] : the assassination of John F. Kennedy - Swanson, James L., 1959- (HarperLuxe, an imprint of HarperCollins Publishers, 2013)
Presents a complete account of the day Kennedy was killed, following the event hour-by-hour, from the Kennedys' arrival in Texas through the shooting in Dealey Plaza to the shocking aftermath.